Assessing Teaching Factory Implementation through Students’ Perceptions: A CIPP Model Approach - Sanatang; Dwi Rezky Anandari Sulaiman; Ninik Rahayu Ashadi; Muh. Ihsan Zulfikar (Information Technology Education Journal, 2025)
This study aims to assess the implementation of the Teaching Factory (TeFa) program through students’ perceptions using the CIPP (Context, Input, Process, Product) evaluation model. The evaluation focused solely on students’ viewpoints as direct beneficiaries of production-based vocational learning, excluding teachers’ and industry partners’ perspectives. A quantitative survey method was employed, involving 70 students from SMKN 10 Makassar, who completed a 12-item questionnaire with high internal reliability (Cronbach’s α = 0.894). Data were analyzed descriptively and through Spearman’s rank correlation to examine the relationships among the CIPP dimensions. The results indicate that students’ perceptions of TeFa implementation were within the “fair to good” range: Context (47.14% fair, 28.57% good, 24.29% very good), Input (41.43% fair, 38.57% good, 18.57% very good), Process (40% fair, 42.86% good, 14.29% very good), and Product (40% fair, 30% good, 24.29% very good). All dimensions showed positive and significant correlations (ρ = 0.619–0.794, p < 0.001), with the strongest relationship between Process and Product (ρ = 0.794), indicating that better learning processes are closely linked to improved learning outcomes. In conclusion, the Teaching Factory program is perceived as moderately effective by students. Improvement efforts should prioritize the Input dimension such as facilities, learning materials, and industrial engagement—and strengthen the Process dimension through enhanced mentoring and integration of production activities. Future research should involve teachers and industry partners to provide a more comprehensive CIPP-based evaluation.